PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA RUMAH MAKAN PADANG TALAGO BIRU PADASUKA - Nurjanah, Siti; Sukmawati, Rina; Muslima, Muslima; Alwi, Subhi (Journal Competency of Business, 2021)
This study aims to explain the effect of product quality and service quality on customer satisfaction at Talago Biru Padasuka Restaurant where the independent variables, namely product quality and service quality, on customer satisfaction as the dependent variable. The research was conducted in Padasuka Village, Cimenyan District, Bandung City, West Java. Data collection methods used are interviews and questionnaires filled out by respondents, namely customers of the blue talagoPadasuka restaurant. Sampling of 100 respondents, in this study using convenience sampling technique. The research method of this thesis is quantitative method, the analysis used includes validity test, reliability test, multiple linear regression analysis, and hypothesis testing which includes F test and T test. correlation coefficient, coefficient of determination. The results showed that with a significance of 0.000 <0.10 then there was a significant effect between product quality and service quality on customer satisfaction.